Sr analyses from only known Scandinavian cremation cemetery in Britain illuminate early Viking journey with horse and dog across the North Sea. - Tessi Löffelmann; Christophe Snoeck; Julian D Richards; Lucie J Johnson; Philippe Claeys; Janet Montgomery (PLoS ONE, 2023)
The barrow cemetery at Heath Wood, Derbyshire, is the only known Viking cremation cemetery in the British Isles. It dates to the late ninth century and is associated with the over-wintering of the Viking Great Army at nearby Repton in AD 873-4. Only the cremated remains of three humans and of a few animals are still available for research. Using strontium content and isotope ratios of these three people and three animals-a horse, a dog and a possible pig-this paper investigates the individuals' residential origins. The results demonstrate that strontium isotope ratios of one of the adults and the non-adult are compatible with a local origin, while the other adult and all three animals are not. In conjunction with the archaeological context, the strontium isotope ratios indicate that these individuals most likely originated from the area of the Baltic Shield-and that they died soon after arrival in Britain. This discovery constitutes the first solid scientific evidence that Scandinavians crossed the North Sea with horses, dogs and other animals as early as the ninth century AD.